P1020-141 Management of Power Sharing in Microgrid - Win, Kaung Htet Naing (2016)
Since the technology is increasing, the demand of power supply needed by various consumers is higher and higher over the years. These days, human are managing no less than one electronic apparatus in their ordinary life for imparting, doing family errands, stimulation and some more. Indeed, basic existences of villagers likewise require major power for illuminating their home around evening time and listening to their most loved project on radio. Along these lines, obviously there are increasingly requests for power supply together with populace and financial development around the world. Oil, coal and natural gases are sources of generating electricity and resulting in higher cost. On the other hand, we can get the sufficient power supply from the Nuclear Energy but it can release harmful radiation during natural disaster or human error. Luckily, there has been found a savvy approach to awesome utilization of free and clean characteristic assets, for example, wind and daylight around us for supplementary power era.